Influence of Magnetic Mirror on the Emission Spectra of DBD Actuator - Aveen Salahuldeen Abdulhamed; Qusay Adnan Abbas (Iraqi Journal of Physics)
The research investigated the effect of magnetic mirror configuration on the properties of plasma formed in a dielectric barrier discharge  (DBD) actuator under atmospheric pressure. The discharge was formed when a high alternating voltage of 22 kV at a frequency of 9 kHz was applied between the electrodes under atmospheric pressure. The magnetic mirror was created when two permanent magnets were placed behind the electrodes. Plasma emission spectra were detected using a photoemission spectrometer at different horizontal distances (D) between the dielectric and the actuator, ranging from 0 to 5 cm. The effect of the magnetic mirror on the plasma properties at different horizontal distances was studied. The results indicated that the value of electron temperature increases with an increase in the horizontal distance at a smaller rate in the presence of the magnetic mirror configuration. The decrease in the surface area of the electrode led to a significant increase in the electron number density in the presence of the magnetic field. The magnetic mirror affected the value of all the plasma properties studied. At the same time, there was no effect on the behaviour of plasma properties in the presence of magnetic mirror configurations.